Leptomeningeal metastasis after effective first-generation EGFR TKI treatment of advanced non-small cell lung cancer. (January 2019) - Wu, Ya-Lan; Zhao, Qian; Deng, Lei; Zhang, Yan; Zhou, Xiao-Juan; Li, Yan-Ying; Yu, Min; Zhou, Lin; Zou, Bing-Wen; Lu, You; Liu, Yong-Mei
Highlights: Leptomeningeal metastasis (LM) has become increasingly common in NSCLC patients. Data are limited about the effect of EGFR TKI on the development of LM. We retrospectively evaluated 420 patients treated with first-generation EGFR TKI. Primary mutation of L858R mark higher risk of LM compared with exon 19 deletions. It highlights the importance of mutation status to biological behaviors of LM. Abstract: Objective: To evaluate the influence of a first-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI) treatment on the clinical features of leptomeningeal metastasis (LM) progression and outcome in advanced non-small cell lung cancer (NSCLC) patients. Methods: We retrospectively evaluated advanced NSCLC patients receiving effective first-generation EGFR TKI treatment ( e.g., treatment > 6 months) at our institution between January 2008 and February 2014. Incidence, time to progression, and treatment outcome of LM were examined. Results: In our cohort, 29/420 patients (6.9%) developed LM. Among the patients harboring L858R or deletion of exon 19 in EGFR, the incidence of LM was 10.7% (21/197) and 3.4% (7/203), respectively (P = 0.006). The median time to LM progression was 16.5 months (95% confidence interval (CI), 11.9–20.8). The median overall survival (OS) after LM diagnosis was 5.2 months (95% CI, 3.2–7.2). In a subgroup analysis, OS was improved in patients with performance status (PS) ≤ 2 vs . PS > 2 (14.2 months vs. 2.3 months, respectively; P < 0.001). OS was also improved among patients who received, rather than did not receive, anti-tumor treatment (6.0 months vs. 1.9 months, respectively; P < 0.001) or whole brain radiotherapy (WBRT) (6.0 months vs . 3.9 months, respectively; P = 0.038). Multivariate analysis indicated that WBRT is a good prognostic factor (P = 0.048), whereas best support care (P = 0.033) and PS > 2 (P = 0.034) were poor prognostic factors. Conclusion: A greater incidence of LM was observed in NSCLC patients harboring EGFR mutations after effective EGFR TKI treatment. In particular, the primary mutation, L858R, potentially predicts a higher risk of LM compared with deletion of exon 19. These results highlight the importance of determining mutation status when evaluating the biological behavior of LM in NSCLC patients who positively respond to EGFR TKI treatment.